Christianity, Presence, and the Problem of History: On Two Forms of Christian Temporality in the Faroe Islands - Jan Jensen (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2021)
In this article, I compare two forms of Christian temproality in the Faroe Islands. In so doing, I problematize some of the ways in which the idea of history has been applied theoretically to studies of churches and congregations in the country. As a remedy to what I see as the shortcomings of social theory when applied to Pentecostal temporality, I propose seeing the latter as a form of extended present. This is set in contrast to dispensationalism, which sees historical and theological time as occuring in a sequential manner. Dispensationalism in this context refers more than anything to the Plymouth Brethren, who make up the biggest group of non-Lutheran Christians in the Faroe Islands. Finally, I reflect on how temporality is shaped by operational goals that differ between similar, yet subtly different Christian practitioners.